«BESTEMSHE» O‘YININING BOLA TARBIYASIDAGI O‘RNI - Dawkeeva, A.; Sh.Shamuratova, M. (SCIENCE and SOCIETY, 2024)
The article discusses the importance of the game in the development of children’s intelligence, the history of the game “Bestemshe”, and the conditions of the game are discussed.
Keywords: intelligence; game; "Bestemshe"; "Togizkumalok"; ability; development